Prevalence of cartilage lesions in foot joints: a test of the concept of limited and progressive lesions. Issue 7 (July 1987) - Youngman, H R; Cooper, F; Byers, P
Abstract : Lesions in the articular cartilage of the joints of the first ray of feet amputated from 54 patients in the age range 10-79 years have been categorised by site, size, and stage of development. The large number of small lesions in early stages of development, appearing from an early age, and the few lesions with extensive bone exposure, occurring only in later years, lend corroboration to the concept of limited and progressive lesions, as established for the hip joint.